Life on the Autism Spectrum Translating Myths and Misconceptions into Positive Futures - Bennett, Matthew (Springer Singapore, 2018)
This book presents a unique exploration of common myths about autism by examining these myths through the perspectives of autistic individuals. Examining the history of attitudes and beliefs about autism and autistic people, this book highlights the ways that these beliefs are continuing to impact autistic individuals and their families, and offers insights as to how viewing these myths from an autistic perspective can facilitate the transformation of these myths into a more positive direction. From 'savant syndrome' to the conception that people with autism lack empathy, each chapter examines a different social myth - tracing its origins, highlighting the implications it has had for autistic individuals and their families, debunking misconceptions and reconstructing the myth with recommendations for current and future practice. By offering an alternative view of autistic individuals as competent and capable of constructing their own futures, this book offers researchers, practitioners, individuals and families a deeper, more accurate, more comprehensive understanding of prevalent views about the abilities of autistic individuals as well as practical ways to re-shape these into more proactive and supportive practices.